An Integrated Framework for Inventory Management Considering Demand and Supply Uncertainties - Singh, Krapal; Solanki, Rahul; Sharma, Kailash Chandra; Singh, Dharamender (Communications in Mathematics and Applications, 2024)
Due to uncertainties on both the demand and supply sides, managing inventories is the most critical and cost-effective challenge faced by supply chain managers in the supply chain network. While inventory management problems with uncertain demand and supply have been covered in the supply chain management literature for a long time, it is fair to say that no one approach can be applied universally across all scenarios. This paper presents an integrated inventory management framework considering non-linear optimization and multi-criteria decisionmaking tools. First, it presents a non-linear model to minimize the total inventory management cost at a centralized location (e.g., distribution center) by considering multiple inventory aggregation scenarios. A series of sensitivity analyses are conducted to examine the impact of demand and supply uncertainties on various key performance indicators related to inventory operations. Lastly, the best inventory aggregation model is selected by using a multi-criterion-based TOPSIS (Technique for order performance by similarity to ideal solution)) analysis.
Keywords: Inventory aggregation; Distribution network; Multi-criteria decision modeling; Supply uncertainties; Demand uncertainties; TOPSIS